Aplikasi DonasiKu Berbasis Android - Muhamad Bahrul Ulum; Habibullah Akbar; Anik Hanifatul Azizah (Universitas Lampung, 2022)
Used goods suitable for use are old goods that have been used once or more than once and are still reasonable to be reused. Most of these used goods are no longer used because they already have other, better substitutes. The current management system for these items is usually only collected and stored in the warehouse or even many are left scattered in the corner of the house until the items become a pile. Rather than being left alone, it is better to reuse these items. For example, by donating items that are still reasonable to be reused to people who need it more. Donations in the form of used goods are still poorly managed, information on donation activities that are held is less spread out and if there is, it is not necessarily reliable. So far, the management of the existing donation system is only for donations in the form of money, so the idea of a solution emerged in the form of developing an Android-based donation system application. To analyze the problem used causal analysis based on the data to be collected. The method used for software development is extreme programming. This application can be a solution to the problem of managing the used goods donation system so that people can make donations in the form of goods that are faster, easier to collect and distribute.